Numerical Study on the Corium Pool Heat Transfer With OpenFOAM - Xi, Zhiguo; Hu, Yuwen; Gong, Houjun; Zhang, Luteng; Ma, Zaiyong; Sun, Wan; Bu, Shanshan; Pan, Liangming (Frontiers in Energy Research, 2020)
In order to ensure the successful implementation of in-vessel retention strategy to terminate molten corium pool evolution, it is necessary to evaluate the heat flux distribution on the lower head wall of reactor pressure vessel. In the present study, the models of internal heating and natural convention buoyancy, as well as the models of WMLES turbulence and phase changing were applied in the open source CFD software OpenFOAM to perform numerical simulations for the COPRA single-layer molten pool experiment. The distributions of temperature, heat flux and crust thickness were obtained. The simulation results were in good comparison with COPRA experimental data, proving the validity of the developed model for corium pool heat transfer characteristics. The simulation method and results could be applied to further in-depth study of thermal behavior in the corium pool.